TRADISI PEMBERIAN GELAR KEPADA SUMANDO DALAM UPACARA PERNIKAHAN ADAT MINANGKABAU DI KOTA BUKITTINGGI - Sri oktaviani; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Tradition is a custom made by a group of people passed down from generation to generation and still be implemented until today. Tradition can not be separated from culture, because the value of the cultural system is the highest and most abstract level of custom. The tradition of awarding titles to sumando is a tradition performed by the Minangkabau community in the city of Bukittinggi, this tradition is done to distinguish men who are married to unmarried men in Minangkabau. This study aims to determine the origin of the awarding of degrees, the process of granting titles, the benefits of the title and the role of the types of sumando in Minangkabau. The theory used in this research is the theory of culture, tradition, customs, and marriage. The method used in this research is qualitative descriptive approach. This research is located in Bukittinggi City. The techniques used in this research are observation, interview, documentation and literature techniques. The results of this study suggest that a Minang man who gets married is given the title by his family for his daily vocation in his wife's neighborhood. The title will continue to apply as long as they are still husband and wife in case of divorce then the title will no longer apply in the family environment.Keywords: Culture, Tradition, Customs, Marriage